The Relative Importance of Worker, Firm, and Market Characteristics for Racial/Ethnic Disparities in Employer-Sponsored Health Insurance - Jennifer Haas; Katherine Swartz (SAGE Publishing, 2007)
The characteristics of an individual, the local labor market, and the firm where an individual is employed each may be associated with racial and ethnic disparities in employer-sponsored insurance (ESI). This study estimates two models to determine the relative effects of each of these three sets of characteristics on the likelihood a worker has a job with ESI. One model has two outcomes: the job comes with ESI or not. The other model has five possible outcomes: the individual is not offered ESI and is uninsured; the individual is not offered ESI and is insured; the individual is offered ESI but turns it down and is uninsured; the individual is offered ESI but turns it down and is insured; and the individual is offered ESI and accepts. Findings indicate that individual characteristics and firm characteristics are more likely to have significant and substantial effects on the probability that a person has ESI, while the effects of market characteristics appear to be conveyed through firm characteristics. Being African American or Hispanic is not significantly associated with having ESI in the two-outcomes model, but in the five-outcomes model each is associated significantly with being uninsured, either because the person has not been offered ESI or has declined offered coverage. Clearly, examining more nuanced outcomes is more informative about the role of race and ethnicity in why working people are uninsured.